2014
DOI: 10.5301/ejo.5000498
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Transscleral Cyclophotocoagulation as Adjuvant Therapy for Refractory Glaucoma in Keratoprosthesis Patients

Abstract: Diode laser transscleral cyclophotocoagulation is an effective treatment option for refractory glaucoma and can be used as a therapy adjuvant to keratoprosthesis. Long-term effects require further clinical observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Perhaps implantable sensors that are capable of measuring intraocular IOPs in KPro eyes may mitigate vision loss from glaucoma in the future. 29 31 No significant association was found between glaucoma shunts and the development of endophthalmitis or KPro extrusions in our series.…”
Section: Discussioncontrasting
confidence: 58%
“…Perhaps implantable sensors that are capable of measuring intraocular IOPs in KPro eyes may mitigate vision loss from glaucoma in the future. 29 31 No significant association was found between glaucoma shunts and the development of endophthalmitis or KPro extrusions in our series.…”
Section: Discussioncontrasting
confidence: 58%
“…Performing successful surgical drainage procedures is difficult because the conjunctival tissue is usually damaged by the scarring and fibrotic nature of the disease itself 1 . Two retrospective case-series studies reported that diode laser transscleral cyclophotocoagulation resulted in IOP reduction in eyes with refractory glaucoma and keratoprosthesis, but only few cases had a diagnosis of OCP 13,14 . Moreover, we found only 1 published case, of secondary glaucoma with silicone oil and OCP, in which MP-TLT was safe and effective for 6 months without exacerbation of the OCP 15 .…”
Section: Discussionmentioning
confidence: 86%
“…1 Two retrospective case-series studies reported that diode laser transscleral cyclophotocoagulation resulted in IOP reduction in eyes with refractory glaucoma and keratoprosthesis, but only few cases had a diagnosis of OCP. 13,14 Moreover, we found only 1 published case, of secondary glaucoma with silicone oil and OCP, in which MP-TLT was safe and effective for 6 months without exacerbation of the OCP. 15 Although the role of cyclophotocoagulation as adjunctive treatment for patients with OCP has been described, there is a lack of evidence of appropriate interventional glaucoma treatment for patients with OCP emphasizes the contribution of this case series and the possibility of MP-TLT to provide safe and efficient care in these difficult cases.…”
Section: Discussionmentioning
confidence: 87%
“…The software can also be extended to the study of a group of patients, database and statistical analysis of a group of patients. Finally, a classifier enabling the classification of specific groups of patients can be proposed [ 31 - 34 ].…”
Section: Resultsmentioning
confidence: 99%